Tinjauan Yuridis Terhadap Perlindungan Hukum BagiKonsumen Transaksi Jual Beli Online (Studi Jual BeliOnline Di Bengkel Knalpot Burnout Exhaust) - Aldi Ferdiansyah; Eti Mul Erowati; Wiwin Mochtar Wiyono (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2019)
To find out how the form of Juridical Review of Legal Protection for Consumers Online Buy and SellTransactions, and to explore various aspects of issues that have been formulated in the formulation ofproblems. To achieve these objectives the author uses a normative juridical approach. The researchspecifications used are descriptive research. The data method is presented in the form of descriptions whichare arranged systematically. The condition of e-commerce on the one hand brings benefits mainly due toefficiency, but on the other hand brings doubt especially to legal issues regarding legal certainty of ConsumerProtection and the validity of business transactions. as stipulated in Article 1 paragraph 1 of Act No. 8 of 1999concerning Consumer Protection which states that